STATE OF HEALTH AND WAYS TO RECOVERY CHILD POPULATION - Khasanova Galina Mamutovna (Modern American Journals, 2025)
Public health is one of the most important values in modern society and a strategic resource for the state. Public health directly impacts socioeconomic development, productivity, and quality of life. Recent decades have seen an increase in chronic diseases, a decline in physical activity, and an increase in stress factors, making public health a particularly pressing issue. Public health promotion involves a range of measures aimed at disease prevention, strengthening physical, mental, and social health, fostering a healthy lifestyle, and creating favorable living conditions. Effective public health promotion requires a comprehensive approach, including physical activity, balanced nutrition, prevention of unhealthy habits, psycho-emotional support, and improvement of the environmental and social environment.